CO-CREATING DIGITAL CURRICULA IN HIGHER EDUCATION an instructors guide to team-based online learning design. - Noghiu, Alain A.; Hilbelink, Amy J.; von Berger, Stacey ([S.l.] : ROUTLEDGE, 2024)
Co-Creating Digital Curricula in Higher Educationis a step-by-step guide to the collaborative design of online and blended curricula in higher education using systematic yet flexible frameworks. While instructors charged with developing and delivering curricula in the remote era may lack formal credentials in learning design, technology management, and institutional leadership, they nonetheless have numerous opportunities to partner with stakeholders who do. This practical, actionable workbook empowers and upskills teaching faculty to partner with their fellow professionals--instructional designers, lead administrators, librarians, and other student support personnel--in co-creative design endeavors that foster outstanding curricula and engaged, successful learners. This holistic, team-oriented approach, intended to ensure curricular cohesion within and between courses, certificates, and programs, is supported by workflows, checklists, workshopagendas, and other field-tested resources.
Keywords: Curriculum planning; EDUCATION / Distance Education & Learning; EDUCATION / Curricula; EDUCATION / Higher